Cost effective and reliable cell based ELISA as an alternative method of flow cytometry for assessment of binding activity of Vedolizumab. Issue 2 (February 2023) - Shalini, Swati; Sharma, Anu; Mishra, Nripendra Nath; Sharma, Ratnesh Kumar; Chander, Harish; Anvikar, Anupkumar R.; Chand, Subhash
Abstract: Vedolizumab is a humanized monoclonal antibody used for inflammatory bowel disease treatment. Vedolizumab binds to the α4β7 integrin complex and inhibits its binding to mucosal addressin cell adhesion molecule-1 (MAdCAM-1). To evaluate the binding efficacy and quality control check of Vedolizumab, flow cytometry is performed by using HuT78 cells. As we know, flow cytometer is costly and require high equipment maintenance with a designated technical manpower to handle it. In this regard, the aim of study was to develop and validate an economical, simple and efficient cell based ELISA assay for potency estimation of Vedolizumab which has not been reported in any pharmacopoeia. The proposed bioassay method was optimized by investigating Vedolizumab binding to α4β7 integrin which is expressed by HuT78 cells. The validation of this method was done at different parameters including specificity, linearity, range, repeatability, precision, and accuracy. The Vedolizumab binding by ELISA results were found specific for Vedolizumab with linearity (R 2 = 0.99) and precision (%Geometric Coefficient of variance) observed for repeatability and intermediate precision were 3.38% and 2.6% respectively. The relative bias was calculated as 8.68% for repeated performances by different analysts and found in accordance with parameter of accuracy as per various pharmacopoeial guidelines. The developed method is established as robust, effective, and less expensive than high maintenance setup like flow cytometry based assay. Graphical abstract: Image 1